Kekerasan terhadap Perempuan dalam Novel Cinta 2 Kodi Karya Asma Nadia - Puspa Indah Utami (LP4MK STKIP PGRI Lubuklinggau, 2020)
The purpose of this study was to gain a deep understanding of women's violence in in the Cinta 2 Kodi novel by Asma Nadia. The research method used content analysis method. The data collection technique used documentation techniques in the form of the Cinta 2 Kodi novel by Asma Nadia. The data in this study are words, phrases and sentences about violence experienced by female characters in the Cinta 2 Kodi novel by Asma Nadia. Data analysis techniques by means of the data description stage, data reduction, data selection, and interpretation. Based on the research results, it was found that the forms of psychological violence against female figures, namely Aryani and Kartika. The psychological violence perpetrated by Aryani's husband caused Aryani to experience an undetectable illness due to prolonged stress. The characters Aryani and Kartika have a patient, sincere, hard work and courage in facing every test in their life. The excellence in packaging stories with conflicts in the form of psychological violence received by female characters in achieving success and the values of patience, sincerity, hard work, and courage that are presented make this novel worthy of being used as a literary reading material at the school and college level.